Dielectric Properties of High Alumina Glass - Farid, S. B. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
High   Alumina   Glasses   "Alumina   Silicate   Glasses"   was prepared by utilizing powder technology technique. The starting materials are wasted soda-lime glass from an industrial site, IraqiÂ Duekhla raw kaolin and small amounts of potassium carbonates.X-ray Diffraction and FTIR analysis show complete vitreous glasses are obtained. Increasing Alumina content plays an obvious role in improving physical and mechanical properties of the prepared high  alumina  glass.   In  addition,  the   increased  alumina  content enhanced the dielectric constant and reduced dielectric loss. These results may be interpreted as due to the bridging bonding of alumina with  both  the   silica  and  the  alkali  oxides;  which  impedes  the alternating electric field.